TO THE PROBLEM OF EXPERIMENTAL-MORPHOLOGICAL STUDIES OF RADIATION-INDUCED THYROID DISEASES - Yu. M. Iryanov; G. N. Filimonova (Сибирский онкологический журнал)
The thyroid gland of 30 4-month-old male Wistar rats was studied. The control group consisted of 5 rats. Twenty-five rats received whole body ionizing radiation with γ-quantum in sublethal dose using the gamma therapeutical apparatus AGAT R1. Animals were killed 2, 5, 10, 15 и 30 days after irradiation (n=5). Histomorphometric analysis included measurements of external follicle diameter, nuclear diameter and area, colloid area, follicular epithelium area, Braun index, nuclear/cytoplasmic ratio and follicular/colloid index. At the end of the experimental study, all morphometric criteria were higher than the control values, especially nuclear area, indicating neoplastic transformation of thyroid. Histograms of distribution of thyrocyte nuclear area were dome-shaped in all days of the experimental study except day 2 characterizing follicular and papillary thyroid cancers. The given work is a prospective experimental-morphological study of radiation-induced neuroendocrine cancers